Buy Now Pay Later (BNPL) Usage and Its Impact on Debt Management Among Malaysian University Students - Lay Hong Tan; Ana Solehah Binti Mohd Yusof; Alyssa Ling Ling Ong; Amedee A/P Suthib; Amirul Aniq Ilham bin Rosmira; Daisy Mui Hung Kee (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
The increased use of Buy Now Pay Later (BNPL) among Malaysian university students has sparked interest in the aspect of financial literacy and the ability to sustain debt. This paper explores the relationship between BNPL usage and level of debt?management among Malaysian university students. Our research designed a quantitative?approach was used through an online survey conducted among the active BNPL user of Malaysian university students. Census results from 150 participants were analyzed to test the purposed hypotheses. The results indicate that students perceived financial management capability, attitude and perceived behavioral control have significant?effects on their behavior toward BNPL services. Low?levels of financial literacy, combined with poor debt repayment behavior, also contribute to higher levels of student debt and higher levels of financial stress. In summary, this study demonstrates that BNPL?services offer access to credit for Malaysian university students but at the same time create financial risk due to their failure in financial literacy. Hence universities and loan institutions should encourage financial literacy to prevent financial stress among?students